2009
DOI: 10.1080/09638180903118694
|View full text |Cite
|
Sign up to set email alerts
|

Accrual Accounting in EU Local Governments: One Method, Several Approaches

Abstract: This paper seeks to measure the degree of accrual implementation in EU local government accounting systems and also tries to give an answer to the question of why accrual accounting has overcome the resistance to other New Public Management (NPM) reforms in countries relatively suspicious of them. We carry out our analysis through the comparison of the accrual accounting legal requirements in force in each country, and the published financial statements, taking the IPSASs of the IFAC as a benchmark. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(228 citation statements)
references
References 57 publications
5
214
0
9
Order By: Relevance
“…Many public accounting scholars highlighted the fundamental difficulties generated by the adoption of accrual accounting (Adam, Mussari, & Jones, 2011;Barton, 2009;Biondi, 2012;Guthrie, 1998;Lapsley et al, 2009;Pina, Torres, & Yetano, 2009) as well as the practical difficulties of public administrations to effectively implement and/or utilize accrual accounting information in decisionmaking processes (Torres, Matsuo, & Pina, 2009). There had only been limited evidence available on the effectiveness of these systems so far.…”
Section: Epsas Ipsas and Accrual Accountingmentioning
confidence: 99%
“…Many public accounting scholars highlighted the fundamental difficulties generated by the adoption of accrual accounting (Adam, Mussari, & Jones, 2011;Barton, 2009;Biondi, 2012;Guthrie, 1998;Lapsley et al, 2009;Pina, Torres, & Yetano, 2009) as well as the practical difficulties of public administrations to effectively implement and/or utilize accrual accounting information in decisionmaking processes (Torres, Matsuo, & Pina, 2009). There had only been limited evidence available on the effectiveness of these systems so far.…”
Section: Epsas Ipsas and Accrual Accountingmentioning
confidence: 99%
“…There is a great number of driving forces, like creation of transpareny [11,12,14,20,[22][23][24]26] or improvement of decision-making [15][16][17][18][19][20][21][22][23][24][25][26]. These driving forces face a huge number of barriers regarding the implementation and use of IT PM concepts.…”
Section: Resultsmentioning
confidence: 99%
“…We found that IT PM is mostly implemented in order to support decision-making [15][16][17][18][19][20][21][22][23][24][25][26], to create transparency [11,12,14,20,[22][23][24]26] as well as to improve accountability [7, 12, 16, 19, 21, 24-28, 37, 38], effectivity [20,22,26,27,[29][30][31] and efficiency [20,22,[26][27][28][29][30][31]. It should contribute to make public administrations more managerial and to make the IT usage more transparent and homogenous.…”
Section: Fig 1 Influencing Factors Driving Forces and Barriers Regmentioning
confidence: 99%
See 2 more Smart Citations